Cytological Aspects on the Effects of a Nasal Spray Consisting of Standardized Extract of Citrus Lemon and Essential Oils in Allergic Rhinopathy. (9th December 2012) - Ferrara, Lydia; Naviglio, Daniele; Armone Caruso, Arturo
Abstract : In this paper, a new formulation of nasal spray was set up based on the extract of lemon pulp, obtained by using a new solid-liquid technology of extraction, added to pure Aloe juice, soluble propoli, and essential oils of Ravensara and Niaouly. It was tested in a clinical study in which 100 subjects were recruited for a period of one month. Nasal scraping was used for collecting samples and after the application of the May-Grünwald Giemsa standard technique, glass slides were analysed by using optical microscope with a 1000x oil immersion. A control group constituted of ten people was recruited as control and this group was administered with physiological solution (saline solution). The comparison of results obtained before and after the application of nasal spray showed a total reduction of eosinophils granulocytes and mast cells; clinical data were confirmed by improvement of clinical pictures of patients. The lemon-based nasal spray was a good alternative to conventional medicine for the treatment of perennial and seasonal allergic and vasomotor rhinopathy.